Strategi Pembelajaran Sejarah Berbasis Historical Thingking Skills untuk Meningkatkan Daya Analisis Siswa - Yuliatin Yuliatin; Razin Faldam; M. Bimo Putra Pratama; Syarifuddin Syarifuddin; Rani Oktapiani (Indo Publishing, 2026)
History learning plays a crucial role in fostering a more realistic awareness and understanding among students. However, in practice, history learning often involves simply delivering material about past events, often referring to and following learning guidelines or syllabi. This article aims to demonstrate the application of a history learning strategy based on Historical Thinking Skills to enhance students' analytical skills and identify barriers and solutions in its implementation. This study employed a qualitative approach with a literature review, referring to scientific journals, books, and other relevant documents. The results indicate that the implementation of Historical Thinking Skills encourages students to think critically through analyzing historical sources, understanding chronology, integrating cause-and-effect relationships, and interpreting various historical perspectives. This strategy empowers students to be more active in the learning process and able to construct arguments based on valid evidence. However, its implementation still faces obstacles such as limited teacher competency, limited learning resources, limited time allocation, and an evaluation system that still emphasizes memorization. Therefore, strengthening teacher competency, utilizing digital technology, developing active learning methods, and updating the evaluation system are needed to support the effectiveness of this strategy.